What Pediatricians Need to Know About the CDC Guideline on the Diagnosis and Management of mTBI - Meeryo C. Choe; Andrew J. Gregory; Tamara M. Haegerich (Frontiers Media S.A., 2018)
Pediatric traumatic brain injury (TBI) is a growing health concern, with over half a million TBI-related emergency department (ED) visits annually. However, this is likely an underestimate of the true incidence, with many children presenting to their pediatrician. The Centers for Disease Control and Prevention (CDC) published a guideline on the diagnosis and management of pediatric mild traumatic brain injury (mTBI). We outline key points and a decision checklist for pediatricians based on this evidence-based guideline.